Revival season : a novel - West, Monica, 1977- (Simon & Schuster, 2021)
"Fifteen-year-old Miriam Horton is the oldest daughter of a Southern Baptist preacher and faith healer. Every summer, the Hortons pack themselves tight in their old minivan and travel through small southern towns for revival season: the time during which Miriam's father holds massive healing services, drawing thousands of people looking to be cured of ailments and disease. This revival season, though, doesn't go as planned, and after one service in which Reverend Horton's healing powers are tested like never before, Miriam witnesses a shocking act of violence behind the revival tent. From that point on, Miriam's belief in her father-and in her faith-begins to waver. When the Hortons return home from the revival circuit, Miriam's confusion only grows as she discovers that she might have the power to heal-even though her father and the church have always made it clear that this power is denied to women. Over the course of the next year, and as a new revival circuit approaches, Miriam must decide between her faith, her family, and her newfound power that might be able to save others, but, if discovered by her father, could destroy Miriam. A story of spiritual awakening and disillusionment in a southern, black, Evangelical community, REVIVAL SEASON is a haunting novel of complicated familial love, a young girl's coming into herself, and the price of being among the community of the faithful"--